Project-Based E-Module as a Learning Medium on the Topic of Fishery Product Processing Waste - Yulda; Bella Sabrina Sitorus; Ferry Dwi Cahyadi; Himawan Prasetiyo; Madea Trianingrum (Jurnal Edutech Undiksha, 2025)
Learning on the topic of Waste Management of Fishery Products in vocational high schools often faces challenges in enhancing students’ practical skills and active engagement. This study aims to develop and evaluate a project-based e-module as an interactive, practical, and contextual learning media. The research employed a Research and Development (R&D) method using the 4D model (Define, Design, Develop, Disseminate). The subjects of the study were teachers and lecturers who acted as validators. Data were collected through observation, interviews, and validation questionnaires, then analyzed descriptively for qualitative data and converted into percentage scores for quantitative data. The results indicate that the developed e-module is feasible for use, with an average eligibility score of 86.6%, and all aspects of media, content, and language fall into the “highly feasible” category. The e-module is equipped with instructional videos, game-based assessments, and project worksheets, and it is disseminated in HTML format and as a mobile application. In conclusion, the project-based e-module is effective as a teaching medium to support contextual and practical learning and can be integrated into vocational learning strategies to enhance students’ practical skills and engagement. Its implications suggest that this media can serve as a reference for teachers, media developers, and policymakers in designing digital project-based learning that aligns with industrial and workplace demands.